2009
DOI: 10.1177/1087057109345525
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Bioactivity of the ToxCast Chemical Library Using BioMAP Primary Human Cell Systems

Abstract: The complexity of human biology has made prediction of health effects as a consequence of exposure to environmental chemicals especially challenging. Complex cell systems, such as the Biologically Multiplexed Activity Profiling (BioMAP) primary, human, cell-based disease models, leverage cellular regulatory networks to detect and distinguish chemicals with a broad range of target mechanisms and biological processes relevant to human toxicity. Here the authors use the BioMAP human cell systems to characterize e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 29 publications
0
100
0
Order By: Relevance
“…In total, there are up to 700 assays or assay end-points being used as part of the ToxCast programme. These cover a large range of technologies, including cell-free biochemical assays, assays targeting nuclear and other receptors and other molecular targets, assays measuring downstream integrated cell processes and model organisms (especially zebrafish) [5,6,[13][14][15][16][17][18][19][20][21][22][23][24]. The complete set of assay descriptions can be found at the ToxCast website.…”
Section: Methodsmentioning
confidence: 99%
“…In total, there are up to 700 assays or assay end-points being used as part of the ToxCast programme. These cover a large range of technologies, including cell-free biochemical assays, assays targeting nuclear and other receptors and other molecular targets, assays measuring downstream integrated cell processes and model organisms (especially zebrafish) [5,6,[13][14][15][16][17][18][19][20][21][22][23][24]. The complete set of assay descriptions can be found at the ToxCast website.…”
Section: Methodsmentioning
confidence: 99%
“…Protein changes upon small molecule treatment are calculated and combined into a BioMAP 1 profile. Multiple studies have demonstrated the ability of these profiles to capture small molecule MoAs [31][32][33][34]. Importantly, although many BioMAP 1 systems monitor inflammatory pathway signaling, characteristic compound profiles can be established for compounds that target other pathways.…”
Section: Moa Elucidationmentioning
confidence: 98%
“…28 In addition, broadening the fingerprint of compound activity by profiling across a range of disease-relevant phenotypic assays can be highly effective, for example, by using the BioMAP platform. 29 In summary, there is a current renaissance in phenotypic screening approaches to identify novel compounds and targets for drug discovery. The mast cell tryptase screen described enables significant diversity screening approaches to be prosecuted, in a time-and cost-efficient manner.…”
Section: Discussionmentioning
confidence: 99%